Onde a luta se travar: a expansão das Assembleias de Deus no Brasil urbano (1946-1980) - Fajardo, Maxwell Pinheiro [UNESP] (2015)
The Assembly of God Church is Brazil's second largest religious group according to the latest Demographic Census. Founded in Belem in 1911, its expansion took place in line with a number of social changes in Brazil during the twentieth century. Among such changes, are highlighted the complementary processes of industrialization and urbanization of the country, evident especially from the second half of the century. It was from this period that the Assemblies of God and other Pentecostal denominations of orientation began to draw attention in the Brazilian religious field. Since 1960 academic studies point to the Pentecostal churches benefited the masses of migrants who came to the cities to provide the manpower for expanding industries, concluding there is a direct link between urbanization and the Pentecostal growth. However, although inserted in the same context, not all denominations have the same growth rate. The Assemblies of God, for example, now have six times more members than the second largest Pentecostal church, also centenary Christian Congregation of Brazil, is having the advantage to have been born around the city. Thus, we start from the assumption that the church member growth in the urban world must be understood not only in the light of external social, but also from the internal dynamics of the Church organization. One of the preponderant factors in this item is a sui generis way Assemblies of God were able to combine their different internal divisions around the same denominational platform without it represented the disintegration or the disintegration of the Church in an institutional fraying process unobservable in any other Brazilian Pentecostal church. Moreover, we also took into account their own cultural codes of the name, born in the overlapping of the Swedish experience of its early leaders, the migratory experience of its members and their own responses developed...